ANALYSE RELEVANT BETWEEN SECTOR FINANCIAL AND SOCIAL OVERHEAD CAPITAL TO PRODUCT OF DOMESTIC BRUTO - Cicih Ratnasih; Yolanda Yolanda (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2018)
The objective of this research is to analyse relevant between sector financial and social overhead capital to product of domestic bruto. This research also the wind know how big influence of either through parsial and also by simultan from variable sector financial and variable social overhead capital to gross domestic product. Method of Analysis used by probit analyse constructively program e-views 5. While result which got from this research is: In Indonesia in the national have been found by that is: by parsia is channel of rate of interest not signifikan, channel of exchange rate of signifikan t-sig 0.00, channel of ekspektasi signifikan t-sig 0.00, channel of price of asset of signifikan t-sig 0.00, channel of credit of t-1 signifikan t-sig 0.00, and variable of social overhead capital signifikan t-sig 0.01. While influence together from free variable to variable trussing of showing result of finding at level of confidence 99 gratuity, with value of F-Sig of equal to 80.23504 and prob 0.00 that together entire/all variable perceived in best model have an effect on signifikan to value of enthusiasm of invesment in IndonesiaThen to variable trussed by GDP indicate that, channel of rate of interest not signifikan, channel of exchange rate of signifikan t-sig 0.05, channel of ekspektasi signifikan t-sig 0.00, channel of price of asset of signifikan t-sig 0.00, channel of credit of t-1 signifikan t-sig 0.00, and variable of social overhead capital signifikan t-sig 0.00. While influence together from free variable to variable trussed by GDP show result of finding at level of confidence 99 gratuity, with value of F-Sig of equal to 1094.857 and prob 0.00 that together entire/all variable perceived in best model have an effect on signifikan to value of GDP in Indonesia Keywords: